SYNERGY BETWEEN BIOENGINEERED NANOPARTICLES AND IONIC COMPLEXES IN ENHANCING THE PERFORMANCE OF ION-SELECTIVE ELECTRODES: A CASE STUDY OF THE DRUG BHDH - Hameed, Mohammed Ahmed; Zadeh, Kamal Ali (Journal for Technology and Science, 2026)
Objective: The present study aims at developing novel nano—electrochemical sensors for the sensitive determination of bromhexine HCl. Method: The method consisted of the formation of “ion pair” complexes, (BHDH-PTA) and (BHDH-PMA), and their incorporation into bio-synthesized silver and iron nanoparticles modified carbon paste electrodes. Results: The analytical performance yielded a broad linear range (10−2 to 10−8 molar) and an ultra-low detection limit of 5.32 × 10−10 molar, a high response speed (3–4 seconds), and operational reliability for over a month. Novelty: Based on Fourier-transform infrared (FT-IR), ultraviolet-visible (UV-Vis), and fluorescence studies, the sensors were confirmed and approved as an effective tool (complexes) for pharmaceutical monitoring and medical diagnosis.